2018
DOI: 10.1101/326017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metanalysis of genome-wide association studies for panic disorder suggest pathways and mechanisms of pathogenesis

Abstract: 20Panic disorder (PD) is characterized by abrupt surges of intense fear and distress. There is evidence 21 for a genetic component in this disorder. We ran a meta-analysis of genome-wide association studies 22 of patients with PD, and found 25 single-nucleotide polymorphisms that were associated with the 23 disorder. Causal gene prediction based on these polymorphisms uncovered 20 hits. Exploratory 24 analyses suggested that these genes formed interactor networks, which was enriched in signaling 25 pathways as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The correlation between homocysteine and SAH levels was reported to be r = 0.413 [29]. SAH exerts feedback inhibition to decrease the activity of Nmethyltransferases (NMTs) that utilize SAM, i.e., catechol-O-methyltransferase (COMT) [30,31] and phenylethanolamine NMT (PNMT) [32], potentially leading to a buildup of dopamine, norepinephrine and epinephrine. In this regard, Silva et al [33] found that a polymorphism in the gene SAH hydrolase (AHCY), which breaks down SAH, was significantly associated with, panic disorder, an endophenotype of psychosis, and Bönig et al [34] presented data showing that elevation of SAH is one of the important factors in the psychosis associated with SAM depletion.…”
Section: Dysregulation Of the Folate Cycle With Psychosis: Increases ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between homocysteine and SAH levels was reported to be r = 0.413 [29]. SAH exerts feedback inhibition to decrease the activity of Nmethyltransferases (NMTs) that utilize SAM, i.e., catechol-O-methyltransferase (COMT) [30,31] and phenylethanolamine NMT (PNMT) [32], potentially leading to a buildup of dopamine, norepinephrine and epinephrine. In this regard, Silva et al [33] found that a polymorphism in the gene SAH hydrolase (AHCY), which breaks down SAH, was significantly associated with, panic disorder, an endophenotype of psychosis, and Bönig et al [34] presented data showing that elevation of SAH is one of the important factors in the psychosis associated with SAM depletion.…”
Section: Dysregulation Of the Folate Cycle With Psychosis: Increases ...mentioning
confidence: 99%
“…Obeid and Herrmann [291] suggested that because betaine is effective in mitigating CNS consequences of high homocysteine levels, it is very likely that the transport mechanism for homocysteine identified by others in synaptosomes [292] contributes to its transport, while Büdy et al [293] demonstrated that homocysteine is indeed transported by the large neutral amino-acid transport (LAT) proteins in endothelial membranes, and also present in the BBB, thereby explaining the efficacy of betaine for psychotic symptoms via its peripheral action. The advantage of betaine for an optimal outcome is that its methyl groups, unlike those generated by 5-methyl-THF, are not involved in the synthesis of epinephrine [32], N-methyldopamine (Figure 2) nor N-methyl-salsolinol [74].…”
Section: Dysregulation Of the Folate Cycle: Neuroprotective Strategiesmentioning
confidence: 99%